Aplikasi Kewirausahaan (K) “CLIPMATE” - Azizatun Fitriani; Muhammad Yasin; Aditya Arga (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This study explores the development and marketing strategy of an entrepreneurial product named CLIPMATE, a multifunctional keychain combining aesthetic design and carabiner functionality. The product targets young consumers, particularly university students, by offering both utility and personal expression. SWOT analysis, market surveys, and profit-loss calculations were conducted to assess market potential and business sustainability. Results indicate that CLIPMATE has promising market opportunities through digital marketing via social media and offline channels such as campus events. The product proves to be profitable with a positive net income and stable growth projection over the next five years. The study concludes that a blend of attractive design, affordable pricing, and strategic marketing are the keys to the success of the CLIPMATE business.